2023
DOI: 10.3390/biomedicines11092352
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis: A New Avenue for Stroke Prevention and Therapeutics

Shin Young Park,
Sang Pyung Lee,
Dongin Kim
et al.

Abstract: A stroke is a serious life-threatening condition and a leading cause of death and disability that happens when the blood vessels to part of the brain are blocked or burst. While major advances in the understanding of the ischemic cascade in stroke was made over several decades, limited therapeutic options and high mortality and disability have caused researchers to extend the focus toward peripheral changes beyond brain. The largest proportion of microbes in human body reside in the gut and the interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…It also enables the investigation of structural changes in the brain and advances imaging techniques for clinical use [ 82 , 83 ]. Preclinical research and computational medicine are critical for unraveling the complexities of neurological and mental disorders, providing critical insights, facilitating treatment testing, and paving the way for novel therapeutics and personalized medicine [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also enables the investigation of structural changes in the brain and advances imaging techniques for clinical use [ 82 , 83 ]. Preclinical research and computational medicine are critical for unraveling the complexities of neurological and mental disorders, providing critical insights, facilitating treatment testing, and paving the way for novel therapeutics and personalized medicine [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genus Ruminococcaceae UCG005 may influence the stroke prognosis by the pathway of glucose and lipid metabolism. Furthermore, ample evidence shows that imbalance in GM contributes to the neuroinflammation and worse stroke outcomes (Huang et al, 2023 ; Park et al, 2023 ). An animal-based study found that maternal sleep deprivation (MSD) caused high expression of pro-inflammatory cytokines in offspring rats Moreover, pro-inflammatory cytokines were positively associated with Ruminococcaceae UCG005 (Yao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been established that inflammation is associated with CBF during normal ageing [103] and across various disease conditions such as acute stroke [104][105][106] and chronic dementia [91,107], but its role during VCI remains unresolved. Our findings highlight the possibility of caspase-1 inhibition as a possible novel anti-inflammatory treatment strategy against cerebral hypoperfusion-induced white matter injury, microglial activation, and tight junction protein deregulation.…”
Section: Discussionmentioning
confidence: 99%